2001
DOI: 10.1023/a:1010225131673
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The efficiency of secretion of Escherichia coli alkaline phosphatase depends on the presence in cells of a cytoplasmic chaperone--protein SecB. Secretion increases in the presence of this chaperone at 30 degrees C, which is the most favorable for the interaction of SecB with the export-initiation domain found previously in the N-terminal region of the mature enzyme. This interaction most likely occurs in the region of the export domain, which is located close to the signal peptide and in complex with a translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“… 25 The high yield of extracellular POD obtained at 25 °C with a relatively low cell density suggested that SecB had a positive effect on POD peptide. 17 To further increase the extracellular POD yield, glycine was added to release the POD within the cell, although glycine inhibited cell growth owing to cell leakage. The high yield of extracellular POD demonstrated the effect of glycine on protein leakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 The high yield of extracellular POD obtained at 25 °C with a relatively low cell density suggested that SecB had a positive effect on POD peptide. 17 To further increase the extracellular POD yield, glycine was added to release the POD within the cell, although glycine inhibited cell growth owing to cell leakage. The high yield of extracellular POD demonstrated the effect of glycine on protein leakage.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Kononova achieved a twofold increase in phoA secretion by increasing the concentration of SecB. 17 Similarly, Zhou obtained 50% increase in human lymphotoxin expression in E. coli by co-expressing SecB. 18 However, excessive chaperone expression could be a burden to the E. coli cells, leading to an increase in the formation of inclusion bodies.…”
Section: Introductionmentioning
confidence: 93%